Intraconal Metastasis Leading to the Diagnosis of Hepatocellular Carcinoma. (11th September 2019) - Madabhavi, Irappa; Mallikarjuna, Vinay Sakaleshpura; Sandeep, K S; Sarkar, Malay; Shah, Mansi; Modi, Mitul
Abstract: Hepatocellular carcinoma (HCC) is the most common malignant cancer of the liver, with intrahepatic and extrahepatic metastasis accounting for 50% to 75% of HCC cases. Lung and regional lymph nodes are the most common sites of metastasis; however, bone, skin, and adrenal glands are rare sites. Orbital metastasis and intracranial invasion are extremely rare and believed to occur in 2% to 3% of patients with systemic cancer. Here, we present a case report of a 72-year-old man evaluated for progressive painful proptosis of the left eye with weight loss, loss of appetite, and generalized weakness of 3 months duration. Physical examination showed a 5.5 × 3.5-cm, firm, mildly tender mass in the upper and lateral part of the left eye with proptosis and hepatomegaly with no ascites. Laboratory investigations were within normal limits except for positive hepatitis B surface antigen and HBV-DNA. CT scan of the head and neck revealed a 5.7 × 4.7-cm heterogeneously enhancing irregular extraconal mass seen in superolateral aspect of the left orbit. Abdominal CT scan showed hepatomegaly with multiple heterogeneous enhancing lesions in the liver. Fine-needle aspiration from the orbital and liver lesions showed individually scattered clusters and sheets of round to polyhedral cells with enlarged, hyperchromatic nuclei, prominent nucleoli, and abundant eosinophilic cytoplasm. Immunohistochemistry showed tumor cells strongly positive for hepatocyte paraffin 1 (HepPar 1) and CD10 but negative for TTF-1, CEA, ALK-1, LCA, vimentin, S-100, and chromogranin, consistent with the diagnosis of HCC. Patient was started on chemotherapy and showed significant improvement with decrease in the size of the liver and orbital mass. Based on the present case and review of literature published since 2009, the current study recommends that metastasis must be considered when diagnosing retrobulbar head lesions in patients with HCC, regardless of contradictory imaging findings and other clinical indicators.